Unlocking crediting opportunities in climate-smart agriculture - Wollenberg, Eva Karoline; Richards, Meryl B.; Costa, Ciniro; Sapkota, Tek Bahadur; Wilkes, Andreas; Reddy, Rama Chandra; Cheng, Zhuo; Tao, Nuyi (Transformative Carbon Asset Facility (TCAF), 2021)
The objectives of this report are to assess the value proposition of results-based carbon finance for CSA, and to provide high-level guidance for the development of CSA carbon crediting programs that considers the characteristics of both the agriculture sector and results-based carbon finance. Target audiences for this report include both stakeholders in climate finance and in the agriculture sector. In particular, the report aims to inform developing country governments about the opportunities for promoting transformative CSA interventions within the framework of results-based finance and its potential positioning in relation to other World Bank financing.